Implementasi E-Kinerja Terhadap Peningkatan Produktivitas Kerja Pegawai di BAPPEDA Kabupaten Simeulue - Zulkifli, Zulkifli; Putri, Cut Mega (Universitas Teuku Umar, 2024)
The E-Kinerja system is the impact of progress that has occurred, to accelerate the development of more advanced communications and technology in the current era. This research aims to identify, analyze and evaluate new technology in increasing ASN/PNS work productivity through the use of E-Kinerja. The method used is a descriptive qualitative approach. This research attempts to present descriptive data on sources or informants, field observations and document research related to the research subject. The implementation of electronic performance in the Simeulue Regency Bappeda has been maximized as an effort to increase ASN/PNS work productivity. This is characterized by new policies being implemented which have a positive impact on increasing employee productivity. The implementation of E-Kinerja at BAPPEDA Simeulue Regency is running smoothly, recording work activity plans is better and reporting is on time. However, there are also employees who often face problems with the system, frequent server errors/downs. Therefore, it is recommended to ensure socialization in the use of E-Kinerja in stages, increasing the bandwidth capacity of the E-Kinerja server so that server errors/server down problems do not occur again.